PERANAN BRIGADIR JENDERAL SOEHARTO DALAM MEMBANGUN KOMANDO CADANGAN STRATEGIS ANGKATAN DARAT (KOSTRAD) TAHUN 1961 – 1965 - Cicih Ninawati; Didin Saripudin; Achmad Iriyadi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This research reviews about the role of a character in the formation and development of the Indonesian Republic military organization on the 1961 – 1965. The background why researcher taking this issue due to the interest in the condition of the development of the Indonesia military organization in the early period of independence. Which is in an all-round hazard and the need for a reliable unit, has forced TNI officer AD to engender a single entity, later called the army General Reserve or CADUAD that no other forerunner of strategic unity and also mobile that right now known as KOSTRAD. The method that used in this research is historical research by doing a four-step research, there are: heuristics, critique, interpretation, and historiography. The results showed that CADUAD is the military organization which was formed and prepared to carry out the operations for the liberation of West Irian that has been delayed since a long time. The establishment of KOSTRAD as one unity of Indonesia’s elite military nowadays that is inseparable from the Research Staff Letter filed by Soeharto who is at that time had risen to become a major general. In the years 1961 – 1965, KOSTRAD has managed to carry out major operations, including Trikora Operation, Dwikora Operation, and operation Completion Problem G 30 S.